Jurisdictional protection against an illicit international treatment of personal data and the new general regulations for data protection of the European Union (Acta Judicial Journal, 2020)
The new General Regulation of Data Protection of the EU (RGPD) has brought with it new rules of international judicial competence: the subject can request the corresponding actions against a data controller or person in charge of data processing before the courts of the state in which the responsible person has an establishment, or before the courts of the state where the interested party has his habitual residence. However, this new solution proposed by the RGPD, in connection with the current norms of international judicial competence, elaborated in the different normative levels (institutional, conventional and autonomous) is not only clearly inadequate to protect the victim of an illegal international treatment of your data, but can even lead to counterproductive results.
Keywords: Data protection, treatment manager, International judicial competence, Applicable law, non-contractual liability.